2022
DOI: 10.1111/apt.17155
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: hepatitis B reactivation in patients receiving biological therapy

Abstract: Background: The use of biologics poses a moderate to high risk for hepatitis B virus reactivation (HBVr) in chronic carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Our study supports the hypothesis that cytokine inhibitors used in patients with psoriasis can cause changes in the immune response, 6 potentially triggering HBVr. Similar to El Jamaly et al's report, which focused on ustekinumab, 1 we found that patients with psoriasis carried a similar risk of HBVr with all kinds of cytokine inhibitors. Among HBsAg+ patients without antiviral prophylaxis, the HBVr rate was 25%.…”
supporting
confidence: 90%
“…Our study supports the hypothesis that cytokine inhibitors used in patients with psoriasis can cause changes in the immune response, 6 potentially triggering HBVr. Similar to El Jamaly et al's report, which focused on ustekinumab, 1 we found that patients with psoriasis carried a similar risk of HBVr with all kinds of cytokine inhibitors. Among HBsAg+ patients without antiviral prophylaxis, the HBVr rate was 25%.…”
supporting
confidence: 90%
“…Additionally, the guideline recommends risk assessment and follow‐up policies based on the potency 6 . One meta‐analysis reported the pooled prevalence of HBV reactivation in patients with HBsAg−/HBcAb+ as follows: 2.6% (95% CI: 1.4%–4.7%, n = 18) for etanercept, 5.0% (95% CI: 2.8%–8.7%, n = 18) for adalimumab, and 7.1% (95% CI: 2.0%–21.7%, n = 4) for golimumab 29 . Etanercept appears to carry a lower risk of HBV reactivation, although this observation may be confounded by other clinical factors, as most of the studies that reported this finding did not adjust for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…6 One meta-analysis reported the pooled prevalence of HBV reactivation in patients with HBsAg−/HBcAb+ as follows: 2.6% (95% CI: 1.4%-4.7%, n = 18) for etanercept, 5.0% (95% CI: 2.8%-8.7%, n = 18) for adalimumab, and 7.1% (95% CI: 2.0%-21.7%, n = 4) for golimumab. 29 Etanercept appears to carry a lower risk of HBV reactivation, although this observation may be confounded by other clinical factors, as most of the studies that reported this finding did not adjust for confounders. Our study accounted for potential confounding variables and found high-potency anti-TNF inhibitors as adalimumab also the independent factor for HBV reactivation.…”
Section: Status a N = 27mentioning
confidence: 93%
See 1 more Smart Citation